2020
DOI: 10.1002/cplu.201900692
|View full text |Cite
|
Sign up to set email alerts
|

Chiroptical Spectroscopic Studies on Lanthanide Complexes with Valinamide Derivatives in Solution

Abstract: Ligands based on 2,2’‐bipyridine and valinamide moieties induce circularly polarized luminescence in their europium complexes. Both the R and S enantiomers of the complexes were successfully obtained. Single‐crystal X‐ray analysis of the racemic crystal confirmed that the ligand is coordinated to the europium ion in a tetradentate fashion. The π‐electronic system of the ligand is co‐planar with the valinamide moiety, and acts as an efficient photoantenna to sensitize europium luminescence by UV excitation. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 39 publications
1
7
0
Order By: Relevance
“…In this contribution, whenever possible, both the transitions were examined and the corresponding values reported in Table 8. The complexes present extinction coefficients in the range 11 000–80 000 m −1 cm −1 , [2, 103, 106–108, 110–117] except for Eu 4 ( L21 ) 4 ( L′ ) 4 and Eu 4 ( L10 ) 4 ( L′ ) 4 , which show extinction coefficients of 600 000 m −1 cm −1 and 800 000 m −1 cm −1 , respectively [118] . In combination with their high quantum yields (0.68 for Eu 4 ( L21 ) 4 ( L′ ) 4 and 0.81 for Eu 4 ( L10 ) 4 ( L′ ) 4 ), they are endowed with outstanding B CPL values (1122 m −1 cm −1 and 3240 m −1 cm −1 , respectively) for the 5 D 0 7 F 1 transition.…”
Section: Cpl Emittersmentioning
confidence: 99%
“…In this contribution, whenever possible, both the transitions were examined and the corresponding values reported in Table 8. The complexes present extinction coefficients in the range 11 000–80 000 m −1 cm −1 , [2, 103, 106–108, 110–117] except for Eu 4 ( L21 ) 4 ( L′ ) 4 and Eu 4 ( L10 ) 4 ( L′ ) 4 , which show extinction coefficients of 600 000 m −1 cm −1 and 800 000 m −1 cm −1 , respectively [118] . In combination with their high quantum yields (0.68 for Eu 4 ( L21 ) 4 ( L′ ) 4 and 0.81 for Eu 4 ( L10 ) 4 ( L′ ) 4 ), they are endowed with outstanding B CPL values (1122 m −1 cm −1 and 3240 m −1 cm −1 , respectively) for the 5 D 0 7 F 1 transition.…”
Section: Cpl Emittersmentioning
confidence: 99%
“…Also, in the field of biomolecules, CPL of green fluorescent protein has been reported, but the g lum value of 1.8 × 10 −3 is small (Goto et al, 2010). In addition, in lanthanoid complexes, the CPL signal associated with f → f transitions has a large g lum , but the CPL band is very sharp (Brittain and Richardson, 1976;Zinna and Bari, 2015;Hasegawa et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…[58] The results showed that whether amino acids induce detectable CPL depends on the ligand of the Eu III complex. Hasegawa et al, [59] Wu et al, [60] and Okutani et al [61] also indicated that the association of amino acids with Eu III complexes may be an effective way to design a CPL system.…”
Section: Cpl Materials Based On Amino Acids Peptides and Proteinsmentioning
confidence: 99%